2019
DOI: 10.3349/ymj.2019.60.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bi-Parametric MR/US Fusion Biopsy for Detecting Clinically Significant Prostate Cancer in Prostate Biopsy Naïve Men

Abstract: PurposeTo explore the effect of bi-parametric MRI-ultrasound (MR/US) fusion prostate biopsy on the detection of overall cancer and significant prostate cancer (sPCa).Materials and MethodsWe examined 140 patients with suspected prostate cancer lesions on MRI from August 2016 to March 2018. All patients had undergone 3T pre-biopsy bi-parametric (T2 weighted and diffusion-weighted) prostate MRI (bpMRI), and their MRI images were evaluated with Prostate Imaging Reporting and Data System (PI-RADS) version 2.0. MR/U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…These disease burden-dependent suggestions rely heavily on understanding and reporting the population under study, and if studies attempting to answer the primary research question do not address this transparently, they will be severely limited. Another study [ 49 ] that was in the minority of papers that reported their PI-RADS 3 population investigated bpMRI and concluded that PI-RADS 3 lesions are expected to require additional tools to supplement bpMRI based on their results as compared to other PI-RADS lesions. This emphasizes the importance of reporting PI-RADS 3 prevalence in a study to enable more accurate research conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…These disease burden-dependent suggestions rely heavily on understanding and reporting the population under study, and if studies attempting to answer the primary research question do not address this transparently, they will be severely limited. Another study [ 49 ] that was in the minority of papers that reported their PI-RADS 3 population investigated bpMRI and concluded that PI-RADS 3 lesions are expected to require additional tools to supplement bpMRI based on their results as compared to other PI-RADS lesions. This emphasizes the importance of reporting PI-RADS 3 prevalence in a study to enable more accurate research conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The technique of targeted MP-MRI/TRUS fusion biopsy is of broad and current interest; it is supported by the joint consensus of the Society of Abdominal Radiology and the American Urological Association (36). The targeted biopsy of suspicious lesions in patients with PSA >4 ng/mL has also been successfully performed by many other clinical applications (37)(38)(39). But a considerable number of patients with PSA in the grey zone have undergone excessive intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate logistic regression analysis revealed that fPSA/PSA, EQS, and PI-RADS score were independent predictors of PCa in grey zone patients (Table 2); we named this the "+EQS model" (Figure 4). In addition, in order to verify the necessity of EQS for PCa prediction, we created the following two models: the "EQS model" that depended 25 [21] 3 [8] 20 [18] 18 [22] 2 [7] 8 [17] 7 [19] 1 [11] 3 73 [47] 62 [52] 11 [31] 49 [45] 40 [49] 9 [ 31 [26] 14 [39] 33 [30] 24 [29] 9 [33] 12 [26] 7 [19] 5 [56]…”
Section: Modelsmentioning
confidence: 99%
“…Recent studies elaborated bi-parametric MRI (bpMRI) is a feasible implement with which to distinguish CSPCa. They recommended using supplemental implements to increase PCa detection in patients with Prostate Imaging Reporting and Data System (PI-RADS v2.1) ≥ 3 4 . In addition, bpMRI has been displayed to have a diagnostic accuracy and PCa detection rate that are equivalent to those of mpMRI.…”
Section: Introductionmentioning
confidence: 99%